Handbook of Environmental Materials Management - Hussain, Chaudhery Mustansar (Springer International Publishing : Imprint: Springer, 2019)
This reference work analyzes and assesses global environmental management techniques for environmental materials with a focus on their performance and economic benefits, proposing eco-friendly solutions and designating policies that will sustain the environment for future generations. It addresses management of environmental materials as not only a complex anthropogenic problem, but also as an expensive problem that needs to be managed sustainably. Simultaneously, it considers the environmental and economic benefits involved in the high levels of investment and operation costs required to develop effective materials collection and management systems in modern society. .